Multicomponent reactions under increased pressure: on the reaction of arylhydrazonals, aromatic aldehydes and malononitrile in Q-Tube - Sadek, Kamal Usef; Selim, Maghraby Ali; Alnajjar, Abdul-Aziz; Atallah, Mohamed; Elnagdi, Mohamed Hilmy (European Journal of Chemistry, 2016)
A novel multi-component reaction between arylhydrazonals, malononitrile and aromatic aldehydes under high pressure utilizing Q-tube was carried out. The reaction of arylhydrazonal (1j) with malononitrile and aromatic aldehydes afforded the corresponding biphenyl derivatives (4). However, compound 1h reacted with malononitrile and aromatic aldehydes (7) to afford pyridazino[5,4,3-de]1,6-naphthyridine-7-carbonitrile derivatives (8). In contrast, the arylhydrazonal (1k) at the same reaction conditions afforded the corresponding pyridazinoquinazoline derivative (22). A rationalization for the difference in behavior for reaction of compounds 1h-k with malononitrile and aromatic aldehydes was postulated. Based on these findings a mechanism to account for the formation of the reaction products is suggested excluding possible initial dimerization of malononitrile as has been previously reported.